Religious clothing in public spaces - Schauer, Pete (Global viewpoints., 2019)
"The diverse viewpoints in this resource address topics such as how tolerance for the wearing of religious clothing differs around the world and whether or not religious clothing should be allowed in public schools. Readers will decide for themselves whether this is an issue of freedom of expression and religion or if it should be viewed as a threat"--